2015
DOI: 10.1159/000441252
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence of Mitochondrial Dysfunction within the Complex Genetic Etiology of Schizophrenia

Abstract: Genetic evidence has supported the hypothesis that schizophrenia (SZ) is a polygenic disorder caused by the disruption in function of several or many genes. The most common and reproducible cellular phenotype associated with SZ is a reduction in dendritic spines within the neocortex, suggesting alterations in dendritic architecture may cause aberrant cortical circuitry and SZ symptoms. Here, we review evidence supporting a multifactorial model of mitochondrial dysfunction in SZ etiology and discuss how these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 123 publications
(183 reference statements)
4
71
0
Order By: Relevance
“…The observation that mtDNA copy number is altered in the brains of subjects with SZ is in the opposite direction of those studies showing reduced density of mitochondria in SZ brain using different methods, i.e. electron microscopy and immunohistochemistry [18,35,36,37,38]. Our measure of mtDNA copy number is quantitative, but does not yield size and location, both of which may be critical aspects of the mitochondrial dysfunction in these cases.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…The observation that mtDNA copy number is altered in the brains of subjects with SZ is in the opposite direction of those studies showing reduced density of mitochondria in SZ brain using different methods, i.e. electron microscopy and immunohistochemistry [18,35,36,37,38]. Our measure of mtDNA copy number is quantitative, but does not yield size and location, both of which may be critical aspects of the mitochondrial dysfunction in these cases.…”
Section: Discussionmentioning
confidence: 55%
“…In a recent review of proteomic, transcriptomic, and genetic studies relevant to SZ, we reported that >250 MitoCarta genes had been shown to be significant in at least one study relevant to SZ [18]. Alterations in these genes could cause mitochondrial dysfunction, although predicting the exact direction and aspect of mitochondrial dysfunction is difficult.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations